NUTRITIONAL AND REMEDIAL POTENTIAL OF AN UNDERUTILIZED FOOD LEGUME HORSEGRAM (Macrotyloma uniflorum): A REVIEW - A. Bhartiya; J. P. Aditya; L. Kant (Journal of Animal and Plant Sciences, 2015)
Underutilized legumes are important group of crops which has special significance in subsistence farming and nutritional security of resource poor masses in developing countries. Among underutilized legumes, horsegram (Macrotyloma uniflorum), familyFabaceae is one of the minor or lesser known neglected legume mainly cultivated in Asian and African countries as a dual purpose crop. It is a climate resilient legume which is well known for its drought hardiness and embraces favourable agronomic features suitable for cultivation on dry lands under poor fertility condition. It is comparable to other commonly consumed pulses in its nutritional value and serves as a cheap source of nutrition for unprivileged rural communities residing in inaccessible areas. Horsegram has excellent therapeutic properties and traditionally used to cure kidney stones, asthma, bronchitis, leucoderma, urinary discharges, heart diseases, piles etc. Besides, it also possess anti-diabetic, anti-ulcer activity and also helps in dietary management of obesity due to the presence of beneficial bioactive compounds. In the present review nutritional composition, antinutritional factors, medicinal properties and its possibilities to be exploited as functional/ medicinal food for health benefits are summarised.
Keywords: Antinutritional factors; Macrotyloma uniflorum; medicinal properties; nutraceutical and nutritional composition